Mesenchymal stem cell mediated effects on microglial phenotype in cuprizone‐induced demyelination model. Issue 8 (8th April 2019) - Barati, Shirin; Ragerdi Kashani, Iraj; Moradi, Fateme; Tahmasebi, Fatemeh; Mehrabi, Soraya; Barati, Mahmood; Joghataei, Mohammad Taghi
Abstract: Microglial cells have an essential role in neurodegenerative disorders, such as multiple sclerosis. They are divided into two subgroups: M1 and M2 phenotypes. Mesenchymal stem cells (MSC), with neuroprotective and immunomodulating properties, could improve these diseases. We evaluate the immunomodulating effects of MSC on microglial phenotypes and the improvement of demyelination in a cuprizone (CPZ) model of multiple sclerosis (MS). For inducing the chronic demyelination model, C57BL6 mice were given a diet with 0.2% CPZ (w/w) for 12 weeks. In the MSC group, cells were transplanted into the right lateral ventricle of mice. The expression of targeted genes was assessed by real‐time polymerase chain reaction. M1 and M2 microglial phenotypes were assessed by immunohistochemistry of inducible nitric oxide synthase (iNOS) and Arg‐1, respectively. Remyelination was studied by luxal fast blue (LFB) staining and electron microscopy (EM). We found that MSC transplantation reduced the expression level of M1‐specific messenger RNA (mRNA; iNOS and CD86) but increased the expression level of M2 specific genes (CD206, Arg‐1, and CX3CR1) in comparison to the CPZ group. Moreover, cell therapy significantly decreased the M1 marker (iNOS + cells), but M2 marker (Arg‐1 + cells) significantly increased in comparison with the CPZ group. In addition, MSC treatment significantly increased the CX3CL1 expression level in comparison with the CPZ group and led to improvement in remyelination, which was confirmed by LFB and EM images. The results showed that MSC transplantation increases the M2 and decreases the M1 phenotype in MS. This change was accompanied by decrease in demyelination and axonal injury and indicated that MSCs have a positive effect on MS by modification of microglia cells. Abstract : In the present study, we established that mesenchymal stem cells (MSCs) therapy can be an appropriate factor for the increase in M2 microglial markers and inhibit proinflammatory cytokines activated by microglia in a CPZ model. Therefore, we suggest that CX3CL1 released by intraventricular transplanted MSCs can moderate the inflammation in microglia and improve the therapeutic potential of MSCs in demyelination situations like multiple sclerosis.